Sistem Informasi Persewaan Alat Pesta Tiga Bintang (Dekorin Aja) Berbasis Codeigniter - Firmansyah, Annas; Hadiono, Kristophorus (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Three- star party outfit reimbursement is one of the party outfit reimbursement places located in the Ngaliyan area, West Semarang. The party outfit reimbursement offers a variety of outfit, similar as tables, chairpersons, canopies, and much further. Not only party outfit, but there are also marriage packages offered. Those still use the homemade system via WhatsApp contact or coming directly to the proprietor's house. Thus it'll impact The period during which the consumer receives schedules, pricing information, and facilities provided by the owner. To solve these problems we must evolve a web-based service system party outfit reimbursement, which aims to help bridge the proprietor if there are any incoming orders to avoid lapping with the schedule and get data snappily. The system erected uses Bootstrap, the CodeIgniter frame, and a MySQL database as data storehouse for the rental reports. And they're using the Waterfall model in making the design inflow and using black box testing. Creating a web- grounded service system for three- star party outfit reimbursement is anticipated to maximize presto and accurate service in propagating provide a wide range of easy-to-understand information for consumers order party outfit.